Pengaruh Financial Knowledge, Money Management Dan Locus Of Control Terhadap Financial Literacy Mahasiswa Perguruan Tinggi Swasta Di Batam - Yosi Afrimayanti; Vargo Christian L Tobing (Prosiding, 2023)
The purpose of this study was to analyze the effect of financial literacy and lifestyle on financial management owned by student. The population in this study were accounting students at Batam University, Universal University, Batam International University, totaling 879 students. The sample used in this study amounted to 275 students using random sampling techniques. The data used in this study are primary data, namely by distributing questionnaire. Data analysis technique used in this case this research is a quantitative data analysis technique using descriptive analysis, instrument testing, classical assumption testing, multiple lineat analysis and hypothesis testing. Hypothesis testing (t test) shows that financial knowledge, money management and locus of control partially have a significant effect on financial literacy. The result of the research on the f test show that financial knowledge, money management and locus of control simultaneously have a significant effect on financial literacy.